27 | ÷ | 13 | = | ( | 80 | − | x | ) | ÷ | ( | x | − | 70 | ) |
Multiply both sides of the equation by: | ( | x | − | 70 | ) |
27 | ÷ | 13 | × | ( | x | − | 70 | ) | = | ( | 80 | − | x | ) |
27 | ÷ | 13 | × | x | − | 27 | ÷ | 13 | × | 70 | = | ( | 80 | − | x | ) |
27 | ÷ | 13 | × | x | − | 27 | ÷ | 13 | × | 70 | = | 80 | − | x |
27 13 | x | − | 1890 13 | = | 80 | − | x |
27 13 | x | + | x | = | 80 | + | 1890 13 |
40 13 | x | = | 80 | + | 1890 13 |
40 13 | x | = | 2930 13 |
x | = | 2930 13 | ÷ | 40 13 |
= | 2930 13 | × | 13 40 |
= | 293 | × | 1 4 |
x | = | 293 4 |
x | = | 73.25 |